Pengaruh Green Culture, Green Loyalty dan Green Environment terhadap Green Consumer Behavior di Café Palmere Jepara - Andriana, Novia Lisa; Arifin, Samsul (Universitas Batanghari, 2024)
A coffee shop is a business that is oriented towards food service. This research aims to analyze the influence of Green Culture on Green Consumer Behavior at Café Palmere Jepara. Analyzing the influence of Green Loyalty on Green Consumer Behavior at Café Palmere Jepara. Analyzing the influence of Green Environment on Green Consumer Behavior at Café Palmere Jepara. The sample for this study was 97 respondents. Partial research results: Green Culture has a positive effect on Green Consumer Behavior. Green Culture is a determinant based on a person's desires and behavior, through family and other institutions, in relationships with other people. A critical marketer in management science must pay attention to cultural values in each marketing area. Partially, Green Loyalty has no effect on Green Consumer Behavior. Green Loyalty is the level of interest in making repeat purchases based on strong environmental characteristics and ongoing commitment to products and services. Partially, Green Environment has no effect on Green Consumer Behavior. The social environment is not an independent function, but is interconnected and produces human behavior.